2018
DOI: 10.17126/joralres.2018.030
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the periodontal clinical effect between conventional and self-ligating brackets: Systematic review and meta-analysis.

Abstract: Introduction: Orthodontists constantly seek to reduce the duration of their provided treatments and the patient's time in the office. For this reason, different bracket systems are currently used in orthodontics; an example is selfligating brackets (SLB) which are believed to offer advantages over conventional brackets (CB). Objective: To evaluate and compare the clinical periodontal effect of CB and SLB through a systematic review and a meta-analysis. Material and Method: A search of the literature was carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Studies were scrutinized by applying inclusion criteria, and 25 systematic reviews were found eligible for full-text assessment (Figure 1). Following full text assessment, 16 articles were included, 9-24 and 8 were excluded. Out of 17 studies, 12 performed a quantitative analysis, 9, 10, 11, 12, 14, 15, 16, 18, 21, 22, 23 and 5 performed a qualitative analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies were scrutinized by applying inclusion criteria, and 25 systematic reviews were found eligible for full-text assessment (Figure 1). Following full text assessment, 16 articles were included, 9-24 and 8 were excluded. Out of 17 studies, 12 performed a quantitative analysis, 9, 10, 11, 12, 14, 15, 16, 18, 21, 22, 23 and 5 performed a qualitative analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Following full text assessment, 16 articles were included, 9-24 and 8 were excluded. Out of 17 studies, 12 performed a quantitative analysis, 9, 10, 11, 12, 14, 15, 16, 18, 21, 22, 23 and 5 performed a qualitative analysis. 13, 17, 19, 20, 24…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings are in contrast to other investigations that declared no differences in the periodontal status in patients who were treated with either SLB or conventional brackets. 39–42 This difference can be explained by the following aspects: variation in baseline confounders, observation timepoints, methodological design, the population studied, units of assessment, statistical analyses, and differences in manufacturer of the brackets. Additionally, meta-analyses described in the literature have expressed the issue of low quality of evidence in studies that evaluated the difference of periodontal status in patients who were treated with SLB or conventional brackets.…”
Section: Discussionmentioning
confidence: 99%